2004
DOI: 10.1098/rspb.2003.2597
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of size–dependent flowering in a variable environment: construction and analysis of a stochastic integral projection model

Abstract: Understanding why individuals delay reproduction is a classic problem in evolutionary biology. In plants, the study of reproductive delays is complicated because growth and survival can be size and age dependent, individuals of the same size can grow by different amounts and there is temporal variation in the environment. We extend the recently developed integral projection approach to include size-and age-dependent demography and temporal variation. The technique is then applied to a long-term individually st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
149
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 94 publications
(152 citation statements)
references
References 31 publications
2
149
0
1
Order By: Relevance
“…For example, it has been shown for semelparous plants that the direction and magnitude of selection on flowering size can vary from year to year [8] and that covariance between demographic rates could amplify the effects of stochasticity [14]. Our qualitative conclusions regarding the importance of non-lethal costs in selecting for delayed reproduction are probably robust to our assumption of environmental constancy, as stochasticity alone does not favour reproductive delay when adult survival exceeds juvenile survival [22], as was the case for O. purpurea (figure 2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, it has been shown for semelparous plants that the direction and magnitude of selection on flowering size can vary from year to year [8] and that covariance between demographic rates could amplify the effects of stochasticity [14]. Our qualitative conclusions regarding the importance of non-lethal costs in selecting for delayed reproduction are probably robust to our assumption of environmental constancy, as stochasticity alone does not favour reproductive delay when adult survival exceeds juvenile survival [22], as was the case for O. purpurea (figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…limitation of regeneration sites and not antagonistic interactions among established individuals) [45]. We tested the assumption that density dependence operates at the establishment stages by examining the relationship between population-level seed production and seedling recruitment [8,16]. Because the first 3 years of development occur below ground, we tested for correlations between total seed production and seedling recruitment 3 years later, separately, for each of the two study sites in each light environment.…”
Section: (C) Parameter Estimation and Detection Of Reproductive Costsmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed size dependence of flowering is gradual, representing possibly a constraint or else a decision that depends on plant size at some time between censuses (Rees et al 1999). We therefore imposed gradual size dependence by holding the size slope fixed at its estimated value and optimizing the intercept and age slope (see Childs et al 2003). Rees et al (1999) compared estimated and ESS flowering strategies and found that plants following the ESS strategy would flower later in life and at larger sizes (on average) than real plants.…”
Section: Evolutionary Analysismentioning
confidence: 99%
“…Under similar assumptions to matrix models, the integral projection model (IPM) predicts a population growth rate l with associated eigenvectors and statedependent sensitivity and elasticity functions (Easterling 1998). An IPM is implemented on the computer as a matrix iteration, but this is just a technique for computing integrals and not a discretization of the life cycle.Several empirical studies have illustrated how a kernel can be estimated from the same data as a matrix model (Easterling et al 2000;Rees and Rose 2002;Childs et al 2003Childs et al , 2004Rose et al 2005). The functions making up the kernel can often be estimated by regression; for example, size-dependent survival and fecundity can be fitted by generalized linear or additive models and growth by parametric or nonparametric regression (Metcalf et al 2003).…”
mentioning
confidence: 99%